Hubungan Tingkat Pengetahuan Dan Gaya Hidup Pada Kejadian Gagal Ginjal Kronik Di Rsud Dr M Yunus Bengkulu - Fikrah Mardatillah Hasanah; Tita Septi Handayani; Ravika Ramlis (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Kidney failure is a form of pathophysiology with various aetiologies that results in decreased kidney function, which can lead to chronic kidney failure (CKF). According to the World Health Organisation (WHO), the increase in the number of patients with kidney failure has become a global health problem, with 850,000 deaths each year. According to the 2018 Riskesdas survey, there has been an increase from 2% to 3.8%. The purpose of this study was to determine the relationship between knowledge levels and lifestyle in cases of chronic kidney failure at Dr. M Yunus Bengkulu Regional General Hospital. This study used an analytical survey with a case-control approach. Purposive sampling was used with 48 respondents, consisting of 24 cases and 24 controls. Data collection was conducted using a questionnaire. Based on the univariate results, it was found that 66.7% of the case group had a good level of knowledge, while 83.3% of the control group did. In terms of lifestyle, 87.5% of the case group respondents had an unhealthy lifestyle, while 91.7% of the control group respondents had a healthy lifestyle. Bivariate analysis of the chi-square statistical test results obtained a p-value of 0.317>a=0.005, meaning that there was no significant relationship between the level of knowledge and the incidence of chronic renal failure at Dr M Yunus Bengkulu Regional General Hospital. while the results of the chi-square statistical test obtained a p-value of 0.000 < α = 0.005, meaning that there is a significant relationship between lifestyle and the incidence of chronic kidney failure at Dr M Yunus General Hospital in Bengkulu.